Chiggerosis: an emerging disease - Meena, Meenu; Meena, Shivraj (International Journal of Research in Medical Sciences, 2016)
Scrub typhus is a zoonotic disease caused by orientia tsutsugamushi,is a very less known cause of fever of unknown origin (FUO). It was first observed in Japan where it was found to be transmitted by mites. The disease was called as tsutsugamushi (tsutsu means dangerous and mushi means insect or mite. This disease is endemic to a geographically distinct region, so called tsutsugamushi triangle, which includes northern Japan and eastern Russia in the North to northern Australia in the South and to Pakistan and Afghanistan in the West. Clinical picture consist of high grade fever, severe headache, myalgia, lymphadenopathy and maculopapular rash on the trunk and then on extremities. A necrotic eschar at the inoculating site of the mite is pathognomic of scrub typhus. Incubation period is 1-3 week. Patients may develop complication like interstitial pneumonia, meningoencephalitis and myocarditis. Diagnosis is often missed because clinical manifestations are similar with other febrile tropical infection.it is diagnosed clinically based on sign and symptoms, serologically molecular methods can be used for their rapid identification as well as for epidemiological purposes. However public health importance of this disease is underestimated because of difficulty in clinical diagnosis and lack of laboratory methods in many geographical areas. Drugs like chloromphenicol and tetracycline effectively treat scrub typhus. No vaccine is available for Scrub typhus but many vaccines using Sta47 and Sta56 antigens are under trial as a recombinant vaccine.